Degradation from Tartrazine Dye Yellow in Solvent Solution via SnO2 NPs - Saad Khalaf Madlool; Waafa Mahdi Salih; Ahmed Mahdi Rheima (Zeta Repository, 2023)
Simple chemical method was used to create tin oxide nanoparticles (SnO2 NPs), which were then annealed at various temperatures for characterisation. X-ray diffraction, scanning electron microscopy, and optical spectroscopy were used to analyze the powders. Due to their low cost, appropriate stability qualities, strong photosensitivity, etc., tin oxide (SnO2) nanoparticles are of tremendous interest in various sectors, including catalytic, electrochemical, and biological applications. The type of transition and band gap of the produced nanoparticles were calculated from the absorption spectra. The optical UV-visible spectrum displays a clearly defined absorption that is significantly blue-shifted in relation to the peak absorption of bulk SnO2, suggesting the impact of quantum size